Multimedia Recognition and Monitoring of Respiration and Heart Rate VO2 Max in Exercise Training Based on Regression Equation - Qiaojuan Liu (Advances in Multimedia)
As an important basis for improving physical fitness and promoting health, the author proposes a research on the identification and monitoring of VO2 max in exercise training based on regression equations. Six female cyclists in province A were used as the experimental subjects. The experimental period was 4 weeks, and the training content was carried out by the coaches according to the training plan. The coefficients of the resulting equations were not significant by a univariate regression analysis of heart rate at LT and V0O. When heart rate is used as the dependent variable, Y represents LT, X represents VT, and heart rate is the independent variable, and unitary regression analysis is performed to obtain the following equation: VT-LT heart rate regression analysis before training: Y = 200.828–0.240XP=0.391>0.05; training post-VT-LT heart rate regression analysis: Y = 239.445–0.469XP=0.073>0.05; VT-LT heart rate comprehensive regression analysis: Y = 218.120–0.343XP=0.043>0.05, the coefficients are significantly different, and the equation is reliable.